Introduction to 2018 special issue of European Security: "ontological (in)security in the European Union". Issue 3 (3rd July 2018) - Kinnvall, Catarina; Manners, Ian; Mitzen, Jennifer
ABSTRACT: The European Union (EU) faces many crises and risks to its security and existence. While few of them threaten the lives of EU citizens, they all create a sense of anxiety and insecurity about the future for many ordinary Europeans. Amongst these crises are the more obvious challenges of sovereign debt and fiscal austerity; refugees from conflicts in Afghanistan, Iraq, and Syria; and the rise of populist far-right parties across Europe. But behind these challenges lie less visible insecurities about economic prospects, social wellbeing, and a widespread expectation that the EU is unable to answer the challenges of twenty-first century global politics. In other words, the greatest security challenge facing people across Europe is not physical, despite the threats of Putin and ISIS, but is a sense of fear and anxiety over their daily lives.